2020
DOI: 10.1002/er.5301
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of solid oxide fuel cell performance by a core‐shell structured catalyst using low concentration coal bed methane fuel

Abstract: A core-shell structured catalyst Ni-BaO-CeO 2 @SiO 2 (@NBC; 7.87% Ni content) with high catalytic activity and thermal stability is prepared and utilized for partial oxidation of methane. The catalyst is introduced into the Ni-8 mol% Ystabilized ZrO 2 anode of a conventional solid oxide fuel cell (CC) by direct spraying (denoted as P-@NBC//CC) and indirect loading as an independent catalyst layer (denoted as Y-@NBC//CC) to improve the coking resistance and cell stability when low concentration coal bed methane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The effects of different factors, including gas composition, temperature, current density, and loading mode of the catalytic layer, on the cell performance of the SOFC utilizing low-concentration CBM were analyzed through a large number of experiments. ,, In addition to CH 4 , there is a certain amount of other gas components in low-concentration CBM, such as oxygen, nitrogen, etc. Some studies have found that O 2 in low-concentration CBM can alleviate carbon formation in the SOFC anodes through oxidation reactions; however, it is generally important not to have more than 5% oxygen in fuels, because excessive oxygen content can cause non-electrochemical oxidation and Ni oxidation, , which will lead to a decline in the cell performance.…”
Section: Frontier Problems Of Sofc Technology Utilizing Low-concentra...mentioning
confidence: 99%
“…The effects of different factors, including gas composition, temperature, current density, and loading mode of the catalytic layer, on the cell performance of the SOFC utilizing low-concentration CBM were analyzed through a large number of experiments. ,, In addition to CH 4 , there is a certain amount of other gas components in low-concentration CBM, such as oxygen, nitrogen, etc. Some studies have found that O 2 in low-concentration CBM can alleviate carbon formation in the SOFC anodes through oxidation reactions; however, it is generally important not to have more than 5% oxygen in fuels, because excessive oxygen content can cause non-electrochemical oxidation and Ni oxidation, , which will lead to a decline in the cell performance.…”
Section: Frontier Problems Of Sofc Technology Utilizing Low-concentra...mentioning
confidence: 99%
“…The DIR-SOFC anode possessed a lower porosity and higher diffusion resistance due to the blockage of anode pores caused by penetrated catalyst particles. 62 However, Fu et al analyzed the differences in electrical performance and temperature distribution between DIR-SOFC and IIR-SOFC by exampling methane-fueled SOFC via experiments and numerical simulations. 63 The results showed that the IIR-SOFC just changed the location of methane reforming as compared to the DIR-SOFC, and the total amounts of H 2 and CO produced were almost the same in these two modes.…”
Section: Integration Of Thermocatalystsmentioning
confidence: 99%
“…Yan et al pointed out that the loading modes of the thermocatalyst significantly affected the SOFC stability. The DIR-SOFC anode possessed a lower porosity and higher diffusion resistance due to the blockage of anode pores caused by penetrated catalyst particles . However, Fu et al analyzed the differences in electrical performance and temperature distribution between DIR-SOFC and IIR-SOFC by exampling methane-fueled SOFC via experiments and numerical simulations .…”
Section: Integration Of Thermocatalystsmentioning
confidence: 99%
“…Ni‐ceramic composites are traditionally applied as anodes for SOFCs and PCFCs 19‐23 . They exhibit good electrochemical performance and catalytic activity toward hydrogen oxidation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Ni-ceramic composites are traditionally applied as anodes for SOFCs and PCFCs. [19][20][21][22][23] They exhibit good electrochemical performance and catalytic activity toward hydrogen oxidation reaction. However, these anodes have several disadvantages, such as degradation in the atmosphere with high water content.…”
Section: Introductionmentioning
confidence: 99%